ANALISIS PSNR PADA STEGANOGRAFI LEAST SIGNIFICANT BIT DENGAN PESAN TERENKRIPSI ADVANCED ENCRIPTION SYSTEM - Rimbun Siringoringo (Universitas Methodist Indonesia, 2016)
Steganography is the art of hiding data on a medium other. Today, steganography is used to secure data by hiding it in other media so that the existence of the message is unintelligible. LSB steagnografi is the simplest method among other methods. LSB steganographic techniques susceptible to steganalisis. In this study the authors combine this with the LSB steganography method by cryptographic techniques. Cryptographic algorithm used is AES. Messages will be inserted first encrypted using the AES method. There are five image dataset being tested. Overall proficiency level datasets have different capacities. There are five types of hidden text with a capacity of 1K, 5K, 10K, 15K and 20K. Testing the quality of the imagebefore and after the embedding process was conducted by PSNR and MD. From the test is known that embedding the message affects the pixel values at specific coordinates on the cover image, the more the characters are pasted on the cover image PSNR value of its smaller, it indicates that the image quality is getting lower and berdanding PSNR value proportionalto the value of MD image.